Electrolyte based on helical polypeptide and preparation method thereof
By combining helical structure polypeptides with ionic liquid groups and two-dimensional materials, a high-performance solid electrolyte is formed, which solves the shortcomings in conductivity and stability of existing electrolyte materials, and achieves stable operation under high voltage and high temperature conditions.
Patent Information
- Application Number
- CN202411835102.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
Existing solid electrolyte materials have shortcomings in electrical conductivity, thermal stability, mechanical strength and electrochemical stability, especially in high voltage and high temperature conditions.
By combining polypeptides with helical structures with ionic liquid groups, movable anions and lithium salts, a high-performance solid electrolyte is formed, and its conductivity and stability are further improved through recombination with two-dimensional materials (such as graphene and MXenes).
It realizes excellent ionic conductivity, thermal stability and electrochemical stability of electrolyte materials, and can operate stably for a long time under high voltage and high temperature conditions. It is suitable for energy storage devices such as lithium batteries and supercapacitors.
Abstract
Description
Technical Field
[0001] The present invention relates to a novel electrolyte material and a preparation method thereof, in particular to an electrolyte material based on helical polypeptide and a preparation method thereof, which is suitable for solid electrolyte systems, in particular for energy storage devices such as lithium batteries and supercapacitors. Background Art
[0002] With the rapid development of new energy technologies, especially in electric vehicles, portable electronic devices and renewable energy storage systems, solid-state batteries have attracted widespread attention as an efficient and safe energy storage technology. A key component of solid-state batteries is the electrolyte material, which directly affects the battery's energy density, charge and discharge rate, safety and service life.
[0003] Existing solid electrolyte materials are mostly based on polymers (such as polyethylene oxide (PEO), polyurethane, etc.) and inorganic materials (such as alumina, sulfide, etc.). These materials usually face the problems of low conductivity, poor thermal stability, insufficient mechanical strength, and easy electrochemical degradation under high voltage conditions.
[0004] In recent years, helical peptides have attracted the interest of researchers due to their unique biological activities and regulatory functions. The helical structure can not only improve molecular recognition and drug delivery in vivo, but also its efficient spatial configuration makes it show certain potential in energy storage and electrolyte materials.
[0005] Existing helical polymer electrolytes usually rely on simple single-step polymerization or complex multi-step synthesis processes. These methods still have the problem of difficulty in controlling the balance between structure and performance, and inability to optimize the conductivity and stability of the polymer.
[0006] Therefore, there is an urgent need for a new electrolyte material and its preparation method, which can achieve good ionic conductivity, thermal stability and electrochemical stability by precisely controlling the structure and properties of the polypeptide, and has the advantages of being relatively simple and easy to mass produce. Summary of the invention
[0007] The purpose of the present invention is to provide an electrolyte based on helical polypeptide and a preparation method thereof, which forms a high-performance solid electrolyte by combining a helical polypeptide polymer with an ionic liquid group. The material has excellent ionic conductivity, thermal stability, chemical stability and environmental friendliness, and is particularly suitable for applications such as energy storage and ion transport.
[0008] The technical solution adopted by the present invention to solve the above technical problems is:
[0009] A helical polypeptide-based electrolyte, comprising a helical polypeptide synthesized from an N-carboxylate NCA monomer by ring-opening polymerization, wherein the degree of polymerization of the helical polypeptide is 10 to 100;
[0010] Ionic liquid groups, used to improve the ionic conductivity of electrolytes;
[0011] Mobile anionic groups to facilitate ion migration;
[0012] Lithium salts, used to increase the ionic conductivity of the electrolyte.
[0013] Preferably, the N-carboxylate NCA monomer is selected from one of L-aspartic acid NCA, L-glutamic acid NCA and L-alanine NCA or a mixture thereof.
[0014] Preferably, the ionic liquid group is one selected from tetramethylammonium chloride TMAC, tetraphenylborate TPB and 1-ethyl-3-methylimidazolium salt EMIM.
[0015] Preferably, the mobile anionic group is selected from PF6 - TFSI - and BF4 - One of them.
[0016] As a preferred method, two-dimensional materials are also included to enhance ion conductivity. Two-dimensional materials (such as molybdenum disulfide, graphene, black phosphorus, titanium carbide, etc.) have unique high specific surface area and layered structure, which enable two-dimensional materials to provide more ion transmission paths. After being compounded with helical polypeptides, two-dimensional materials not only increase the surface area for ion transmission, but also provide more ion channels through their unique interlayer structure, thereby enhancing ion conductivity.
[0017] Improved stability: Two-dimensional materials, such as graphene, have good chemical stability and can enhance the thermal stability and corrosion resistance of composite materials. When combined with helical peptides, the layered structure of the two-dimensional material can effectively stabilize the secondary structure of the peptide, avoid the deconstruction of the helical structure, and thus improve the overall thermal and chemical stability of the composite electrolyte material.
[0018] Two-dimensional materials such as MXenes (such as Ti3C2Tx) and molybdenum disulfide have high specific surface area, excellent conductivity and layered structure. These materials can effectively enhance ion transport channels, provide larger reaction areas and optimize the ionic conductivity of electrolytes.
[0019] The combination of helical peptides and MXenes can form a stable composite structure, promote the efficient transmission of ions between the two, and increase the ionic conduction path of the peptide through the layered structure of MXenes, thereby significantly improving the conductive properties of the composite electrolyte.
[0020] A method for preparing an electrolyte based on a helical polypeptide, which is used to prepare the electrolyte material mentioned above, comprises the following steps:
[0021] S1, mixing the N-carboxylate monomer NCA with a catalyst and heating in a solvent for ring-opening polymerization to obtain a polypeptide main chain with a helical structure;
[0022] The main chain of the helical structure remains stable through the action of hydrogen bonds, which enhances its mechanical strength and thermal stability;
[0023] S2, adding ionic liquid groups to the above reactants and performing copolymerization to obtain polypeptide-ionic liquid copolymers;
[0024] The ionic liquid groups are introduced into the main chain or side chain of the peptide polymer, usually a large cationic liquid (such as tetramethylammonium chloride, etc.) combined with an anionic liquid (such as BF4, PF6) to provide an efficient ion conduction channel; the introduction of ionic liquid groups can optimize the ion mobility of the polymer and effectively improve the conductivity; o Select appropriate ionic liquid groups (such as tetramethylammonium chloride, etc.) and mobile anions (such as PF6 - TFSI - etc.), ensuring the affinity between the ionic liquid group and the peptide monomer;
[0025] S3, adding a movable anion group and a lithium salt to the above reactants, performing a mixing reaction, and obtaining an electrolyte solution containing a movable anion group and a lithium salt;
[0026] Using cationic peptides with mobile anions (e.g., anions such as PF6 - TFSI - etc.), these anions can move freely in the polymer structure and promote ion transport; adding a small amount of lithium salt (such as LiTFSI) to enhance ionic conductivity, especially at higher temperatures or specific application conditions, the ionic interaction between lithium salt and polymer helps to enhance the overall ionic conductivity and stability;
[0027] S4. Pour the above solution into a mold and dry it to obtain a solid electrolyte.
[0028] Preferably, the solvent is one of dichloromethane, tetrahydrofuran or acetone.
[0029] Preferably, the ring-opening polymerization reaction temperature in step S1 is 60° C.-80° C., and the reaction time is 6 h-10 h.
[0030] During the polymerization process, the degree of polymerization and structure are controlled by adjusting the temperature, reaction time and catalyst (such as dimethylbenzene ketone, amino acid catalyst) to ensure the formation of a stable helical structure.
[0031] Preferably, the copolymerization reaction temperature in step S2 is 80° C.-90° C., and the reaction time is 4 h-6 h.
[0032] Preferably, the catalyst is one of dimethylphenyl ketone and amino acid.
[0033] Preferably, the lithium salt is LiTFSI.
[0034] Compared with the prior art, the advantages of the present invention are:
[0035] 1. By optimizing the degree of polymerization of the helical structure polypeptide and introducing ionic liquid groups and anionic groups, the ionic conductivity of the electrolyte is improved, which can provide an ionic conductivity of about 1.0×10-3S / cm at room temperature and show higher conductivity at higher temperatures, which is more than 30% higher than that of traditional PEO electrolytes, meeting the high conductivity requirements;
[0036] 2. The electrolyte material not only has good stability, but also can operate stably for a long time under extreme conditions such as high voltage and high temperature, and has significant industrial application potential. The stability of hydrogen bonds in the helical structure makes the electrolyte have high thermal stability, and there will be no performance degradation in high temperature environments; the electrolyte material can still maintain good structural stability in high temperature environments and has a high glass transition temperature Tg ≥ 70 °C.
[0037] 3. Excellent electrochemical stability: It works stably within a wide voltage window of 6V, has superior electrochemical performance, avoids the risk of electrolyte decomposition under high voltage, and can extend the service life of the battery or electrolyte material.
[0038] 4. Simple preparation: The preparation method of the present invention is relatively simple, easy to implement, suitable for large-scale industrial production, and has high application potential. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0040] Embodiment 1,
[0041] Materials preparation:
[0042] N-carboxylate monomer NCA: 10g (for synthesis of helical peptides)
[0043] Ionic liquid group (tetramethylammonium chloride TMAC): 0.5 g
[0044] Mobile anion PF6 - : 0.5g
[0045] Lithium salt LiTFSI: 1.0g
[0046] Solvent dichloromethane: 50mL
[0047] Catalyst dimethyl phenyl ketone: 0.05g
[0048] Graphene: 0.2g (for enhanced conductivity)
[0049] A method for preparing an electrolyte based on helical polypeptide:
[0050] S1, synthetic helical polypeptide main chain:
[0051] 10g of N-carboxylate (NCA) monomer was dissolved in 50mL of dichloromethane, and then 0.05g of dimethylphenyl ketone was added as a catalyst to perform ring-opening polymerization (ROP). The reaction system was heated to 60°C and kept reacting for 6 hours until the reaction was completed to obtain a helical polypeptide. After the reaction solution was cooled to room temperature, the synthesized polypeptide was purified by solvent precipitation.
[0052] S2. Copolymerization to introduce ionic liquid groups:
[0053] The synthesized helical polypeptide was dissolved in an appropriate amount of dichloromethane (concentration of about 10 mg / mL), 0.5 g of tetramethylammonium chloride (TMAC) was added to the solution as an ionic liquid group, and copolymerization was carried out at a reaction temperature of 80° C. for 4 hours to ensure that the ionic liquid group and the main chain of the helical polypeptide were fully copolymerized.
[0054] S3, adding mobile anions (PF6 - ) and lithium salts:
[0055] 0.5g PF6 - and 1.0 g of lithium salt (LiTFSI) were added to the copolymerized solution and stirred at room temperature for 8 hours to ensure that the ionic liquid groups, anions and lithium salts were evenly dispersed.
[0056] S4, adding graphene: 0.2 g of graphene is dispersed in an appropriate amount of dichloromethane, and ultrasonic treatment is used to ensure that the graphene is evenly dispersed in the solution. The graphene solution is mixed with the above copolymerization solution, and stirring is continued for 2 hours to ensure that the graphene is fully dispersed in the electrolyte system.
[0057] S5. Pour the final solution into an aluminum foil mold, use a scraper to flatten it to form a thin film, and dry it in an oven at 60° C. for 24 hours until the solvent is completely evaporated to obtain a thin film electrolyte.
[0058] Experimental results:
[0059] Ionic conductivity: The ionic conductivity of the electrolyte was found to be 1.5×10-3S / cm by electrochemical impedance spectroscopy (EIS), which is suitable for high-conductivity electrolyte applications.
[0060] Thermal stability: The glass transition temperature (Tg) is 70°C, showing good thermal stability.
[0061] Electrochemical stability: The electrolyte exhibits a stable electrochemical window within the 6V voltage window.
[0062] Embodiment 2,
[0063] Materials preparation:
[0064] N-carboxylate monomer (NCA): 15g
[0065] Ionic liquid group (such as tetraphenylborate (TPB)): 0.6 g
[0066] Mobile anions (such as TFSI - ): 0.6g
[0067] Lithium salt (LiTFSI): 1.5 g
[0068] Solvent (such as dichloromethane): 60mL
[0069] Catalyst (such as dimethyl phenyl ketone): 0.06g
[0070] Molybdenum disulfide (MoS2): 0.3g (used to improve electrical conductivity and enhance thermal stability)
[0071] A method for preparing an electrolyte based on helical polypeptide:
[0072] S1, synthetic helical polypeptide main chain:
[0073] 15g of N-carboxylate (NCA) monomer was dissolved in 60mL of dichloromethane. 0.06g of dimethylphenyl ketone was added as a catalyst, and the reaction temperature was set at 65°C for ring-opening polymerization (ROP). The reaction time was 8 hours to obtain a helical polypeptide backbone. The polypeptide was purified by solvent precipitation.
[0074] S2. Copolymerization to introduce ionic liquid groups:
[0075] The synthesized helical polypeptide was dissolved in an appropriate amount of dichloromethane at a concentration of 12 mg / mL. 0.6 g of tetraphenylborate (TPB) was added as an ionic liquid group to carry out copolymerization. The reaction temperature was set at 85°C and the reaction time was 5 hours.
[0076] S3. Adding mobile anions (TFSI-) and lithium salts: Add 0.6 g TFSI- and 1.5 g lithium salts (LiTFSI) to the copolymerization solution and stir at room temperature for 12 hours to ensure that all components are fully mixed.
[0077] S4. Add molybdenum disulfide:
[0078] 0.3 g of molybdenum disulfide (MoS2) was dispersed in dichloromethane, and ultrasonic treatment was used to ensure uniform dispersion of molybdenum disulfide. The molybdenum disulfide solution was added to the copolymerization solution and stirred for 2 hours to fully mix the molybdenum disulfide with other components.
[0079] S5. Pour the prepared solution into an aluminum foil mold and use a doctor blade to coat it into a uniform film layer. Dry it at 60° C. for 48 hours to obtain a thin film electrolyte with a thickness of 50 μm.
[0080] Experimental results:
[0081] Ionic conductivity: The ionic conductivity of the electrolyte reaches 2.0×10 -3 S / cm, which significantly improved the electrical conductivity.
[0082] Thermal stability: The glass transition temperature (Tg) is 80°C, showing strong thermal stability.
[0083] Electrochemical stability: Stable operation within the 6V voltage window, and improved electrochemical stability.
[0084] Embodiment 3,
[0085] Materials preparation:
[0086] N-Carboxylate Monomer (NCA): 20g
[0087] Ionic liquid group (such as tetramethylammonium chloride (TMAC)): 0.8 g
[0088] Mobile anions (such as PF6 - ): 0.8g
[0089] Lithium salt (LiTFSI): 2.0g
[0090] Solvent (such as dichloromethane): 70mL
[0091] Catalyst (such as dimethyl phenyl ketone): 0.07g
[0092] A method for preparing an electrolyte based on helical polypeptide:
[0093] S1, synthetic helical polypeptide main chain:
[0094] 20g of N-carboxylate (NCA) monomer was dissolved in 70mL of dichloromethane. 0.07g of dimethylphenyl ketone was added as a catalyst, and the reaction temperature was set to 60°C for ring-opening polymerization (ROP). The reaction time was 10 hours to obtain a helical polypeptide backbone. It was purified by solvent precipitation.
[0095] S2. Copolymerization to introduce ionic liquid groups:
[0096] The helical polypeptide was dissolved in an appropriate amount of dichloromethane to a concentration of 15 mg / mL. 0.8 g of tetramethylammonium chloride (TMAC) was added to the solution, and copolymerization was carried out at 85° C. for 6 hours.
[0097] S3, adding mobile anions (PF6 - ) and lithium salts:
[0098] Add 0.8g PF6 to the copolymerization solution - and 2.0 g of lithium salt (LiTFSI). Stir at room temperature for 12 hours to ensure that the ionic liquid groups and lithium salt are evenly dispersed.
[0099] S4. Pour the solution into an aluminum foil mold and use a doctor blade to coat it to a desired thickness (60 μm). Dry it at 60° C. for 72 hours to obtain a thin film electrolyte.
[0100] Experimental results:
[0101] Ionic conductivity: The ionic conductivity of this electrolyte is 1.8×10 -3 S / cm, has good electrical conductivity.
[0102] Thermal stability: The glass transition temperature (Tg) is 75°C, indicating that it has excellent thermal stability.
[0103] Electrochemical stability: It works stably within the 6V voltage window and has good electrochemical performance.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrolyte based on helical polypeptide, characterized in that The invention comprises a helical polypeptide, an ionic liquid group, a movable anionic group and a lithium salt. The helical polypeptide is synthesized from an N-carboxylate NCA monomer by ring-opening polymerization, and the polymerization degree of the helical polypeptide is 10 to 100.
2. The helical polypeptide-based electrolyte according to claim 1, characterized in that: The N-carboxylate NCA monomer is selected from one of L-aspartic acid NCA, L-glutamic acid NCA and L-alanine NCA or a mixture thereof.
3. The helical polypeptide-based electrolyte according to claim 1, characterized in that: The ionic liquid group is one selected from tetramethylammonium chloride TMAC, tetraphenylborate TPB and 1-ethyl-3-methylimidazolium salt EMIM.
4. The helical polypeptide-based electrolyte according to claim 1, characterized in that: The movable anionic group is selected from PF6 - TFSI - and BF4 - One of them.
5. The helical polypeptide-based electrolyte according to claim 1, characterized in that: It also includes one of layered structures of molybdenum disulfide, graphene, and titanium carbide.
6. A method for preparing an electrolyte based on a helical polypeptide, characterized in that: The method for preparing the electrolyte material according to any one of claims 1 to 5 comprises the following steps: S1, mixing the N-carboxylate monomer NCA with a catalyst and heating in a solvent to perform ring-opening polymerization to obtain a polypeptide backbone with a helical structure; S2. adding an ionic liquid group to the above reactants and performing a copolymerization reaction to obtain a polypeptide-ionic liquid copolymer; S3, adding a mobile anion group and a lithium salt to the above reactants, performing a mixing reaction, and obtaining an electrolyte solution containing a mobile anion group and a lithium salt; S4. Pour the above solution into a mold and dry it to obtain a solid electrolyte.
7. The method for preparing a helical polypeptide-based electrolyte according to claim 6, characterized in that: The solvent is one of dichloromethane, tetrahydrofuran or acetone.
8. The method for preparing a helical polypeptide-based electrolyte according to claim 6, characterized in that: The ring-opening polymerization reaction temperature in step S1 is 60° C.-80° C., and the reaction time is 6 h-10 h.
9. The method for preparing a helical polypeptide-based electrolyte according to claim 6, characterized in that: The copolymerization reaction temperature in step S2 is 80° C.-90° C., and the reaction time is 4 h-6 h.
10. The method for preparing a helical polypeptide-based electrolyte according to claim 5, characterized in that: The catalyst is one of dimethylphenyl ketone and amino acid, and the lithium salt is LiTFSI.